2017
DOI: 10.1096/fasebj.31.1_supplement.639.10
|View full text |Cite
|
Sign up to set email alerts
|

Low Birth Weight is More Common in Food Insecure Pregnant Malawian Women with Moderate Malnutrition

Abstract: AimTo determine if food insecurity for pregnant women with moderate malnutrition (MAM) affects gestational weight gain, infant weight and length.MethodsThis randomized controlled trial enrolled 1872 pregnant women with MAM, defined as mid‐upper arm circumference (MUAC) between 20.6 and 23.0 cm. Women aged 16 to 45 years enrolled at approximately 24 weeks gestation. Household Food Insecurity Access Scale (HFIAS) survey was obtained at enrollment. Women returned every two weeks for measurements and received supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In yet another facility based unmatched case–control study, food insecurity was one among many factors associated with LBW babies [ 50 ]. A similar study in Malawian women further demonstrated a strong association between food insecurity for mothers and LBW babies [ 51 ].…”
Section: Discussionmentioning
confidence: 87%
“…In yet another facility based unmatched case–control study, food insecurity was one among many factors associated with LBW babies [ 50 ]. A similar study in Malawian women further demonstrated a strong association between food insecurity for mothers and LBW babies [ 51 ].…”
Section: Discussionmentioning
confidence: 87%